Algorithm to assess the presence of Aspergillus fumigatus resistant strains: The case of Norwegian sawmills. Issue 5 (4th May 2022) - Viegas, Carla; Almeida, Beatriz; Aranha Caetano, Liliana; Afanou, Anani; Straumfors, Anne; Veríssimo, Cristina; Gonçalves, Paulo; Sabino, Raquel
ABSTRACT: Association between selection pressure caused by the use of azole fungicides in sawmills and the development of fungal resistance has been described. The aim of this study was to implement an algorithm to assess the presence of Aspergillus section Fumigati resistant strains in sawmills. Eighty-six full-shift inhalable dust samples were collected from eleven industrial sawmills in Norway. Different culture media were used and molecular identification to species level in Aspergillus section Fumigati was done by calmodulin sequencing and TR34 /L98H and TR46 /Y121F/T289A mutations were screened by real-time PCR assay and confirmed by cyp 51A sequencing. Six Fumigati isolates were identified as A. fumigatus sensu stricto and two of these grew on azole-supplemented media and were further analyzed by real-time PCR. One was confirmed to be a TR34 /L98H mutant. The obtained results reinforce the need to assess the presence of A. fumigatus sensu stricto resistant isolates at other workplaces with fungicide pressure.